Peran dan Desain Bahan Ajar dalam Pembelajaran Bahasa: Telaah Teoritis dan Praktis dalam Konteks Pendidikan Lokal - Zulfiqar, Ahid Ilham; Fuadah, Intan Samrotul (Indo-MathEdu Intellectuals Journal, 2026)
This article aims to analyse the role and principles of teaching material design in modern language learning. This study uses a literature review method with critical analysis of the teaching material design theory proposed by Richards and the principles of language learning according to Tomlinson, and relates them to teaching practices in the context of Indonesian education. The study focuses on the format and function of teaching materials, the use of authentic and artificial materials, criteria for evaluating and selecting materials, context-based adaptation strategies, and principles of effective teaching material design. The results of the study show that language learning becomes more effective when teaching materials are designed through a targeted combination of structured artificial materials and contextual authentic materials, with the teacher playing a key role in the process of adapting teaching materials. These findings emphasise the importance of strengthening teachers' competencies as evaluators, adapters, and designers of teaching materials so that language learning can be relevant, contextual, and meaningful.